Coccidioidomycosis Causing Osteomyelitis of the Hand in an Immunocompetent Patient. (September 2015) - Berli, Jens U.; Campbell, Wayne N.; Katz, Ryan D.
Coccidioidomycosis osteomyelitis is a rare entity considered even more rare when identified in the immunocompetent patient. In non-endemic areas, the diagnosis of a fungus-causing osteomyelitis is often delayed or overlooked. This results in delayed or inappropriate treatment. We present the case of a 35-year-old immunocompetent male immigrant from India who was ultimately diagnosed as having Coccidioidomycosis immitis osteomyelitis of his ring finger metacarpal. His initial surgery included drainage and bacterial cultures only. When he failed to improve, he presented for a second opinion. The patient's origin and travel history coupled with the appearance of rapid bone destruction on plain radiographs prompted a second operation for tissue biopsy and culture for bacteria, fungus, and mycobacteria cultures. This case highlights the importance of a thorough clinical history in deriving an appropriate differential diagnosis prior to surgical intervention.